Approach for quality detection of food by RFID‐based wireless sensor tag. Issue 25 (1st December 2013) - Nguyen, Son Dat; Pham, Thong Tien; Fribourg Blanc, Eric; Le, Ngan Nguyen; Dang, Chien Mau; Tedjini, Smail
Abstract : A novel wireless sensor for the detection of food quality is presented. The main idea is to transform radio frequency identification (RFID) tags into RFID sensors, owing to a specific design of the tag antenna. From knowledge of the variation of the permittivity of food over time through experimental characterisation, it is possible to detect the time from which the food becomes improper for consumption based on the read‐range measurement of the designed sensing tags. This low‐cost ultra‐high frequency (UHF) RFID passive sensor was designed and experimentally tested on plastic‐film‐wrapped beef meat. The overall agreement between the experimental and simulation results shows the potential of this technique for real‐world applications in food traceability.